Integrating Cyberfeminism and Technofeminism to Address AI Industry Challenges - Lubis, Akhyar Yusuf; Badry, Ahmad Ibrahim; Yuliatiningtyas, Solikhah (Golden Ratio of Data in Summary, 2025)
This article investigates how cyberfeminism and technofeminism intersect with the AI industry, particularly in addressing the complex ethical and social challenges that accompany AI’s rapid growth across various sectors. By analyzing scholarly research, industry insights, and practical case studies, this study outlines how feminist frameworks can meaningfully influence and reshape AI development. Central to this discussion is the role of cyberfeminism and technofeminism in exposing and countering biases and ethical issues embedded within AI technologies. These feminist movements advocate for transparency, inclusivity, and responsible AI, supporting a technology landscape that values equity and human well-being. Additionally, the article provides real-world examples of feminist-led initiatives within the AI field, showcasing their potential to drive positive transformation. Through an intersectional lens, this study emphasizes the need for AI systems that are sensitive to diverse community needs and experiences. The article calls on industry stakeholders to adopt feminist principles and intersectional methods to foster a more equitable, just, and accountable AI ecosystem.